PROCEDURES FOR THE LEGAL TRANSFORMATION OF STATE-OWNED ENTERPRISES: A COMPREHENSIVE LITERATURE REVIEW OF THE CHANGE FROM PERJAN TO PERUM OR PERSERO BASED ON ARTICLE 92 OF LAW NO. 19 OF 2003 AND ITS IMPLEMENTATION IN MODERN SOE GOVERNANCE - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
State-Owned Enterprises (SOEs) underwent a fundamental legal transformation from the form of Government Enterprises (Perjan) to Public Enterprises (Perum) or Limited Liability Companies (Persero) based on Article 92 of Law No. 19 of 2003, which required legal status adjustments through Government Regulations. This normative-doctrinal literature review analyses the transformation procedures—including ministerial policy decisions, the transfer of assets, finances and employees, and the continuation of rights and obligations—as well as their implementation in modern SOE governance through the principles of good corporate governance (GCG). The results show that the transformation has succeeded in increasing operational efficiency and GDP contribution, as in the cases of PT Kereta Api Indonesia (Persero) and PT Pegadaian (Persero), although the challenges of PSO-profit dualism and political intervention remain. This study recommends strengthening SOE holding regulations and GCG certification to support the Indonesia Emas 2045 vision.